Analisa sistem kerja photovoltaic berdasarkan sudut kemiringan menggunakan monocrystalline dan policrystalline - La Rudawin; Nurlaila Rajabiah; Dwi Irawan (Universitas Muhammadiyah Metro, 2020)
Photovoltaic work systems were analyzed based on its slope angle using monocrystalline and polycrystalline to the power generated. This research is a direct action research (Action Research) namely the design approach stage, tool fabricating phase, and the tool testing phase. The testing phase conduct measurements and analyses, the stages and process of designing tools, and system testing tools that include measurements of light intensity, temperatur, current, and Voltage. The first year observation data in the form of slope measurements of 00, 300, 600, that conducted for 15 days at 08:00-16:00 every hour, data, Voltage, temperatur, and light intensity. The results of this study in the form of the maximum acquisition of light intensity received by the solar panel on the slope angle. Solar radiation intensity carried out a great effect on the power (Pout) of Photovoltaic cell output, wherein the morning solar radiation intensity is greater with the result that it produces greater power. Sunlight intensity in the afternoon and evening tends to decrease so that the power that is halted is smaller. The magnitude of slope angle carried great effect on the output power (Pout) of Photovoltaic cells, where the greatest power at an angle of 0ᵒ obtained namely maximum Pout 17.01 W and maximum Voltage Vm is 19.5 V. While the minimum power Pout is 12 W and minimum Voltage Vm 14 V which obtained at an angle of 60ᵒ. Greatest efficiency (η) of Photovoltaic cells at an angle of 0ᵒ obtained. This is caused by the Voltage and current output of Photovoltaic cells Vm and Im which tend to decrease when the value of the Photovoltaic cell angle is large. Therefore the efficiency of the Photovoltaic cell output will decrease along with the decrease in the Photovoltaic cell output power.Keywords: Photovoltaic, slope angle, power, efficiency.